2019
DOI: 10.6000/1929-7092.2019.08.52
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Pass-through on Domestic Inflation: Oil Importing Versus Oil Exporting Countries

Abstract: Previous studies have evident the effects of oil price changes on domestic inflation. However, such effects may vary due to oil dependency factor. This paper extends the examination on two panel groups, namely the oil importing and oil exporting countries. Each group consists of ten countries. Besides, we also compare the relative effects of oil price with other shocks (domestic output, exporter's production cost and real exchange rate) on domestic inflation (consumer price and producer price). Our results cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Secondly, [ 33 ] suggested that international oil prices have not risen for domestic oil consumers, which has pushed up inflation. Third, [ 3 ] considered both of those effects would have an overall impact on the general growth of GDP, either an immediate change in fuel prices, an adjustment within the rise in oil prices, or both [ 34 ]. This study considered the Keynesian theory to reassess the relationship between income and consumption of South Asian households.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, [ 33 ] suggested that international oil prices have not risen for domestic oil consumers, which has pushed up inflation. Third, [ 3 ] considered both of those effects would have an overall impact on the general growth of GDP, either an immediate change in fuel prices, an adjustment within the rise in oil prices, or both [ 34 ]. This study considered the Keynesian theory to reassess the relationship between income and consumption of South Asian households.…”
Section: Introductionmentioning
confidence: 99%